Project Report Sonic Analysis Of Machine Parts - HARSHA N RANE,GOPAL G,MANOHARA H and VARUN DHEERENDRA (2011)
INTERNAL GUIDE : Lakshmi C R EXTERNAL GUIDE : Nallusamy V USN NO : 1MJ08EC032, 1MJ08EC027, 1MJ08EC030 and 1MJ05EC027 CARRIED OUT AT : Mvj Coolege Of Engineerig Channasandra Near ITPB Bangalore-560 067 ACC NO : PR1851 Project Report CD No : RC42
Keywords: Sonic Analysis Of Machine Parts